The importance of comunication in the Nursing-Patient relationship - Batista-Reyes, Yaisemys; Guirola-Fuentes, Jurek; Robles-Mirabal, Violeta (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2025)
The importance of effective communication in the nurse-patient relationship within the healthcare context is essential to ensuring not only the patient's physical well-being, but also their emotional and mental well-being. The nurse-patient relationship is a critical component of the Nursing Care Process. Nurses, as professionals responsible for providing direct care, are often the ones who spend the most time with patients. This frequent interaction gives them a unique perspective to understand patients' needs and concerns. However, this relationship is not limited to the simple transmission of information; it is a dynamic, two-way process that significantly impacts treatment outcomes.